Consumption Pattern of Timber and Fuelwood in Community Forests: a case study from Sindhupalchok District - Lamichhane, D (Banko Janakari, 2009)
The study was carried out in four community forest user groups (CFUGs) of Sindhupalchok district of Nepal with a view to find out the consumption pattern of forest products especially timber and fuelwood from the community forests (CFs). A set of structured questionnaires was used to collect data from the respondents of the selected CFUGs. Four CFUGs were randomly selected from among those meeting the predetermined criteria such as: more than 5 years old, regularly harvesting timber and fuelwood, and active in forest management. With a 20% sampling intensity, 103 respondents were identified from the groups for household visit and personal interview. Records of forest product distribution together with a checklist of secondary data were obtained from the District Forestry Office (DFO) and the CFUG records. This data were analyzed using both descriptive and inferential statistical analysis. Results indicated that there was no significant difference in the use of timber and fuelwood among the users. Similarly, there was no correlation between the number of livestock and use of firewood. However, there was a strong relationship between the number of livestock and fodder trees on their farmland. There was a higher demand for fuelwood than timber but the pine-dominant community forests were found to be producing more timber, thereby creating a big gap between the demand and supply of firewood. However, the supply of timber was comparatively consistent with demand. Keywords: Community forest user group, demand and supply, farmland, fuelwood, timber doi: 10.3126/banko.v19i1.2179 Banko Janakari, Vol. 19, No. 1, 23-28